Highly efficient yellow‐orange emission and superior thermal stability of Ba2YAl3Si2O12:Ce3+ for high‐power solid lighting - Huang, Dayu; Liu, Zhiyuan; Wang, Bo; Che, Hailin; Zou, Man; Zeng, Qingguang; Lian, Hongzhou; Lin, Jun (Journal of the American Ceramic Society, 2021)
With great economic benefits, white LEDs (w‐LEDs) have aroused worldwide attention. For phosphor‐converted w‐LED, highly efficient emission and good thermal stability of phosphor are significant parameters in practical application. Here, a yellow‐orange garnet‐structural phosphor, Ba2YAl3Si2O12:xCe3+ (x = 0‐0.1) (BYAS:xCe3+) was developed by solid solution design. The broad emission spectrum of the as‐synthesized phosphor could guarantee the effective increase of the color rendering index when it is combined with the InGaN blue chip. Benefiting from the garnet‐type highly rigid framework, BYAS:xCe3+ exhibits an excellent thermal stability (50%@673K of the initial integrated intensity at 280 K) as well as high absolute quantum efficiency (80.4%@460 nm excitation light). Utilizing the approach of “phosphor‐in‐glass” (PiG), a high‐power warm w‐LED is achieved based on a blue LED plus PiG and the illuminance of this w‐LED device can be as high as 4227 lx. Design Ba2+‐Si4+ pairs‐doped YAG matrix, Ba/Y ions are randomly distributed in the dodecahedral sites, and Si ions occupy Al2 sites, obtaining high rigidity structure with ultra‐high thermal stability.